How Wireless Power Charging Technology Affects Sensor Network Deployment and Routing - Bin Tong; Zi Li; Guiling Wang; Wensheng Zhang (2010 IEEE 30th International Conference on Distributed Computing Systems, 2010)
As wireless power charging technology emerges, some basic principles in sensor network design are changed accordingly. Existing sensor node deployment and data routing strategies cannot exploit wireless charging technology to minimize overall energy consumption. Hence, in this paper, we (a) investigate the impact of wireless charging technology on sensor network deployment and routing arrangement, (b) formalize the deployment and routing problem, (c) prove it as NP-complete, (d) develop heuristic algorithms to solve the problem, and (e) evaluate the performance of the solutions through extensive simulations. To the best of our knowledge, this is the first effort on adapting sensor network design to leverage wireless charging technology.